PROGRESIFITAS HUKUM PENGEMBALIAN DEVIDEN SAHAM INTERIM PERSEROAN TERBATAS PADA UUPT NO.40 TAHUN 2007 - Bella Mutiara Wahab (Legal Standing : Jurnal Ilmu Hukum, 2021)
AbstractProgressive law must place the law in a very close position with the law's community or stakeholders. This position is called responsive, progressive law and is always associated with stakeholders' reality and needs to create justice and happiness as law aspired itself. Also, progressive law emphasizes social integration to overcome public moral insularity.Starting from the viewpoint of progressive law, the author looks at the laws and regulations that discuss the return of interim dividends as stated in the Limited Liability Company Law No. 40 of 2007, article 72, article 72 states that companies allow rules related to dividend distribution in a temporary (interim) way. The article is then interpreted as that if the company has positive profits, the company is allowed to distribute dividends before the company closes the book at the end of the year, provided that the board of directors officially announces the distribution with the approval of the GMS that the positive profits obtained by the company before closing the book will come as dividends interim. As a result, the company competes to distribute interim dividends to increase and show its credibility to investors. It was recorded on the Indonesian stock exchange (IDX) that in September 2020, 73 companies distributed interim dividends.However, article 72 paragraph 5 of the Limited Liability Company Law No. 40 of 2007 explains that if after the company distributes interim dividends to shareholders and at the end of the closing of the annual book the company suffers a loss, the shareholders must return the dividends they have received. If the shareholder does not return it, the directors and commissioners are jointly responsible for covering the company's losses.This viewpoint is the basis for finding the location of the value and form of legal progressivity regarding the mechanism of interim share dividends in limited liability companies as stated in UUPT No.40 of 2007 Article 72 using a normative research method with a conceptual approach.